Mechanism of microscopic behind the influence of stress loading on gas adsorption by coal - Zhihui Wen; Shuqian Guo; Yanxia Zhao; Yanping Wang; Ran Jia; Jiangang Ren (Scientific Reports, 2025)
Abstract This study aims to explore the mechanism behind the influence of stress on gas adsorption by coal during deep mining and improve the accuracy of gas disaster prevention and control. To achieve this aim, thermodynamic analysis was conducted on the process of gas adsorption by loaded coal, and modified thermodynamic model proposed by previous scholars. It is found that stress plays an important role in gas adsorption by coal. In addition, isothermal adsorption experiments were performed on coal samples under different stress states with the aid of a coal rock triaxial adsorption and desorption experimental device. Based on the experimental results, the variations in adsorption capacities of coal samples under different stress loads were obtained. Finally, molecular dynamics simulation of gas adsorption was conducted by taking lignite as the research object. The microscopic mechanism of gas adsorption by loaded coal is elucidated from the perspectives of isothermal adsorption parameters of the loaded coal, isothermal heat of adsorption, and the changing law of the probability density distribution of adsorbed gas molecules. The research findings are anticipated to offer theoretical and practical guidance for the prevention and control of gas disasters in deep coal mines and the extraction of coalbed methane.